The Effect of Capital Intensity and Accounting Conservatism on Tax Avoidance with Company Size as a Moderating Variable - Yusril; Lince Bulutoding; Nur Rahmah Sari (Journal of Applied Taxation and Policy, 2026)
Tax avoidance remains a critical issue for companies, including state-owned enterprises (SOEs), as taxes are perceived as a burden that reduces profitability. This study aims to examine the effect of capital intensity and accounting conservatism on tax avoidance, as well as to analyze the moderating role of company size in SOEs listed on the Indonesia Stock Exchange (IDX) during the 2020–2022 period. Using a quantitative approach, this study analyzes secondary data obtained from audited annual financial statements, with 48 firm-year observations selected through purposive sampling. Multiple linear regression and Moderated Regression Analysis (MRA) were employed to test the hypotheses. The results indicate that capital intensity has a negative and significant effect on tax avoidance, while accounting conservatism does not have a significant effect. Furthermore, company size significantly moderates the relationship between capital intensity and tax avoidance as well as between accounting conservatism and tax avoidance. These findings highlight the importance of asset structure and firm scale in shaping tax avoidance behavior and imply the need for stronger oversight and improved transparency in corporate tax management.